(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective of study: Determine the training needs of medical staff at Thanh Hoa Oncology Hospital in 2024. Research subjects and methods: a cross-sectional descriptive study on 434 medical staff working at Thanh Hoa Provincial Oncology Hospital. Results: 82.3% of hospital staff have participated in advanced training courses, of which 76.2% were sent by their agencies. The training needs of staff are very large, up to 76.3%. The need for online training accounts for 47%, the purpose of going to school to improve qualifications accounts for 93.1% and 72.8% of staff want to be supported with all course fees. Conclusion: Hospital staff have a very large training need and mainly want to be trained online and have their tuition fees supported.